2020
DOI: 10.1080/09602011.2020.1776135
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of aphasia therapy dosage in the first six months of stroke recovery

Abstract: Aphasia research uses the length of time within rehabilitation sessions as the main measure of dosage. Few papers detail therapeutic ingredients or outline the number of times these were delivered over the treatment period. The present observational study identified therapeutic ingredients in the Very Early Rehabiltiation in SpEech (VERSE) trial and explored the dosage provided using a model of cumulative intervention intensity (CII). Therapists video recorded one therapy session per week and 53 (12%) randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…• Motor rehabilitation: Scrivener et al 31 demonstrated that in a 30-minute observation period with early subacute stroke patients, exercise repetitions ranged from 4 up to 369. • Language rehabilitation: Brogan et al 32 showed that in a 51-minute session, use of 2 key ingredients was varied with total verbal utterances ranging from 21 to 944 and cues used with success ranging from 0 to 196. Therefore, we need an approach that captures the interrelatedness of the multiple dimensions of nonpharmacological intervention dose.…”
Section: Challenge 2: Dose Is Multidimensionalmentioning
confidence: 99%
“…• Motor rehabilitation: Scrivener et al 31 demonstrated that in a 30-minute observation period with early subacute stroke patients, exercise repetitions ranged from 4 up to 369. • Language rehabilitation: Brogan et al 32 showed that in a 51-minute session, use of 2 key ingredients was varied with total verbal utterances ranging from 21 to 944 and cues used with success ranging from 0 to 196. Therefore, we need an approach that captures the interrelatedness of the multiple dimensions of nonpharmacological intervention dose.…”
Section: Challenge 2: Dose Is Multidimensionalmentioning
confidence: 99%
“…Further, the treatment fidelity reported here was completed at the macrostructure level. Previously published work [22,23] presents finer grained, utterance level analyses and adds nuanced therapeutic information to the efficacy picture. Finally, the receipt of treatment and enactment of treatment skills areas of Bellg et al [5] were not measured in this study and so cannot be commented on.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Further studies should i) focus on the proportion of time given to language-related therapeutic activities, rather than the less-exact 'number of hours' measure, ii) obtain more detail on the diverse contexts in which therapy may occur and (iii) ask patients to formally record their "therapy homework" and other language practice activities. By quantifying the number of specific therapeutic inputs, a measure of cumulative intervention intensity can be calculated (Brogan et al, 2020), and evaluated alongside all the other factors found to influence inter-patient variability in recovery (e.g., patients' physical and mental health, cognitive abilities, level of engagement, demographics, social support). Ultimately, this will improve predictions of outcomes and the response to therapy at the individual patient level (Aguilar et al, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%